HUMAN LITERACY IN TANTRI: PEREMPUAN YANG BERCERITA AS A CHARACTER EDUCATION MEDIA - Ni Nyoman Ayu Suciartini; I Nyoman Subrata (INTERNATIONAL JOURNAL ON HINDU CULTURE, 2024)
Balinese society considers ancestral narratives as an inevitability. Ancestral narratives, adapted into various forms such as traditions, rituals, songs, performances, dances, and even classical or modern literary works, always hold a place of significance and attention among the people. One of the well-known traditional ancestral narratives is the story of Tantri. This Tantri narrative has inspired artists, writers, and cultural scholars to present more modern works. One of them is the literary work titled "Tantri: Perempuan yang Bercerita." The aim of this study is to analyze the value of human literacy in the literary work " Tantri: Perempuan yang Bercerita." The method used is qualitative descriptive method. In the narrative of this novel, the values of human existence or human literacy are prominent. One of them is the significant role of women in maintaining civilization. The important role of women, depicted in the character of Tantri, who can overcome all the evil desires of a Prabu Eswaryadala with her words and language. This story also builds an understanding of human literacy contextualized with the present era, where women have equality and can strive for justice based on their knowledge and life skills. Values of character education, leadership, wise attitude towards changes and developments in technology and the digital world also become important values in the narrative of Tantri.